The Effectiveness of Leaflet and Video Educational Media Toward the Knowledge of Type 2 Diabetes Mellitus Patients - Anggraeni, Novia Dwi; Novaria, Astri Ayu; Utami, Riana Pangestu; Wiryanto, Wiryanto (Journal of Health and Nutrition Research, 2024)
This study aims to know the effectiveness of leaflets and video educational media in the knowledge of type 2 diabetes mellitus patients in the inpatient room of RSUD Beriman Balikpapan. The methodology used is a quasi-experimental study with a pretest and posttest research design with control group. The intervention group used video media and the control group used leaflet media. The results obtained were that the average patient knowledge increased in the experimental group, which was 50.90, ± 8,228 SD before the intervention, increasing to 81.37, ± 9,615 SD after the intervention. In the control group, the mean knowledge of patients before the intervention was 55.75, ± 7,036 SD, increasing after the intervention to 84.18, ± 9,895 SD. The P-Value value is 0.000 < 0.05 from the results of the analysis of the difference in knowledge between the experimental group and the control group after the intervention shows that there is a significant difference between the two; so that H0 is rejected and Ha is accepted. This means that nutritional counseling using video and leaflet media can increase knowledge about Diabetes Mellitus and video media is more effective than leaflet media. The providing nutritional counseling using video media was more effective than using leaflet media in increasing the knowledge of Diabetes Mellitus patients in the inpatient ward of the Beriman Balikpapan Regional Hospital.